Salivary Oxytocin and Vasopressin Levels in Police Officers With and Without Post‐Traumatic Stress Disorder. (October 2015) - Frijling, J. L.; van Zuiden, M.; Nawijn, L.; Koch, S. B. J.; Neumann, I. D.; Veltman, D. J.; Olff, M.
<x xml:space="preserve">Abstract</x> Post‐traumatic stress disorder (PTSD) is characterised by symptoms associated with maladaptive fear and stress responses, as well as with social detachment. The neuropeptides oxytocin (OT) and arginine vasopressin (AVP) have been associated with both regulating fear and neuroendocrine stress responsiveness and social behaviour. However, there is only limited evidence for dysregulated peripheral OT and AVP levels in PTSD patients. The present study aimed to investigate basal salivary OT and AVP levels in trauma‐exposed male and female police officers with and without PTSD. Saliva samples were collected during rest and OT and AVP levels were determined using a radioimmunoassay. Men and women were analysed separately, having adjusted for differences in trauma history, and for hormonal contraception use in women. The results showed that male PTSD patients had lower basal salivary OT levels, and did not differ in AVP levels compared to male trauma‐exposed healthy controls after adjusting for childhood emotional abuse. There were no significant differences in basal salivary OT and AVP levels in women. Our findings indicate potential dysfunctioning of the OT system in male PTSD patients. Future studies are needed to replicate these findings and to further unravel the relationship between the OT and AVP systems, sex, trauma history and PTSD.